Polypharmacy And The Use Of Potentially Inappropriate Medications Among Aged Inpatients - Marcus Vinicius Palmeira Oliveira; David Costa Buarque (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: In Brazil, 70% of older adults have at least one chronic disease and, of these, 60% use more than four medications regularly, characterizing polypharmacy. Potentially inappropriate medications (PIMs) are used by 40% of this population. Both polypharmacy and PIM use are associated with negative outcomes, such as increased frequency of drug interactions, falls, frailty, malnutrition, and in some cases, death. METHOD: This was a cross-sectional study with retrospective data collection of all older patients admitted for clinical reasons to a tertiary care hospital in Brazil from March 2015 to February 2016. We evaluated patients for the presence of polypharmacy and PIM use, correlating these findings with other variables of interest. RESULTS: The medical records of 456 patients were analyzed. Mean patient age was 83 years, and 71.3% were women. The mean Charlson comorbidity index (CCI) was 2.38, and dementia was the most prevalent comorbidity (36.6%). Polypharmacy was present in 56.5% of patients, and 46.4% of them used at least one PIM. Antipsychotics were the most frequently used PIM (46.2%), followed by benzodiazepines (33.0%). Drug interactions were detected in 53.5% of patients. The presence of polypharmacy was associated with the use of PIMs (p < 0.001). Additionally, both polypharmacy and PIM use were associated with drug interactions (p < 0.01), poorer functional status (p < 0.01), and higher CCI (p = 0.015). CONCLUSION: In this study population, the prevalence of polypharmacy was 56.5%, and 46.5% of cases included the use of PIMs. Both conditions were associated with drug interactions, poorer functional status, and higher CCI.